Posisi Keris Pada Masyarakat Jogja Modern - Endah Endrawati (Jurnal Komunikasi, 2015)
AbstractKeris supposedly as a status symbol of nobility, is now confronted by alternative culture (mass culture) as an alternative preservation. Dagger that is said as magical objects and sacred believed to be heirlooms. Now, as kris is an alternative object of merchandise ready for sale and waiting buyers. Kris phenomenon in modern times, its development was encouraging. Keris enthusiasts and observers began to shift from elders to young people, students or youth. The values of humanism on the kris, Religious Values, their belief in the power of man. Value Philosophy of the keris lajer (straight) people live should have a clear direction or purpose. Keris Luk, in achieving the purpose of life, human beings should not be sakleg flexible. History values, the height of science and technology owned civilization wrought iron bangsaatau ancestors of our ancestors. Economic value, collections are becoming increasingly scarce, the higher the price (investment), also overcome unemployment for furniture craftsmen keris. In addition, the value of Psychology, generating confidence and a spirit of confidence for success.AbstrakKeris yang konon sebagai lambang status kebangsawanan, kini dihadapkan oleh budaya alternatif (budaya massa) sebagai salah satu alternatif pelestarian. Keris yang konon sebagai benda bertuah dan dikeramatkan diyakini sebagai pusaka. Kini keris merupakan benda alternatif seolah barang dagangan siap jual dan menunggu pembelinya. Fenomena keris di zaman modern,  perkembangannya  cukup menggembirakan. Peminat dan pemerhati keris mulai bergeser dari sesepuh kepada generasi muda, mahasiswa atau pemuda. Nilai-nilai humanisme pada keris yakni, Nilai Religi, adanya kepercayaan akan kekuatan manusia. Nilai Filosofi adanya keris lajer (lurus) manusia hidup harus punya arah atau tujuan yang jelas. Keris Luk, dalam meraih tujuan hidup, manusia harus luwes tidak sakleg. Nilai Histori, ketinggian ilmu pengetahuan dan teknologi tempa besi yang dimiliki peradaban nenek moyang bangsaatau leluhur kita. Nilai Ekonomi, koleksi yang semakin lama semakin langka akan semakin tinggi harganya (investasi), juga mengatasi pengangguran bagi perajin perabot keris. Selain itu, Nilai Psikologi, pembangkit kepercayaan diri dan semangat keyakinan untuk sukses.